2015
DOI: 10.1136/tobaccocontrol-2015-052547
|View full text |Cite
|
Sign up to set email alerts
|

Retailer compliance with tobacco control laws in New York City before and after raising the minimum legal purchase age to 21

Abstract: Several aspects of tobacco control appear to have deteriorated in NYC. Greater attention to monitoring retailer compliance with all tobacco regulations will be important for Tobacco 21 laws to be effective in reducing youth access to tobacco products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…In particular, we assume that 15% of smokers will respond to increased prices by seeking out opportunities to avoid the new prices. MPL price analyses in Malaysia 35 and New York City, 36 however, indicate that the per cent of illicit (or below minimum price) sales only increased by 3-5 percentage points following policy implementation, suggesting we may have underestimated the modelled policies' impact on prices. In reality, the amount of policy avoidance will likely vary by state, based in part on differences in prices in, and distances to, nearby cigarette markets, 37 38 and by income levels, smoking intensity and self-reported price levels prepolicy.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, we assume that 15% of smokers will respond to increased prices by seeking out opportunities to avoid the new prices. MPL price analyses in Malaysia 35 and New York City, 36 however, indicate that the per cent of illicit (or below minimum price) sales only increased by 3-5 percentage points following policy implementation, suggesting we may have underestimated the modelled policies' impact on prices. In reality, the amount of policy avoidance will likely vary by state, based in part on differences in prices in, and distances to, nearby cigarette markets, 37 38 and by income levels, smoking intensity and self-reported price levels prepolicy.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study found that in California, nearly 50% of tobacco and vape shops did not check IDs when underage decoys attempted to purchase vaping products 10. When a T21 law passed in New York City, a study investigated retailer compliance with ID checks and found that compliance actually decreased after T21 policies were enacted (from 71% compliance to 62%) 16. It was also found that independent retailers of tobacco products had significantly lower compliance rates compared with chain stores 16.…”
Section: Discussionmentioning
confidence: 99%
“…When a T21 law passed in New York City, a study investigated retailer compliance with ID checks and found that compliance actually decreased after T21 policies were enacted (from 71% compliance to 62%) 16. It was also found that independent retailers of tobacco products had significantly lower compliance rates compared with chain stores 16. Independent retailers may be reluctant to check IDs of individuals if they are similar in age to the retailers 17.…”
Section: Discussionmentioning
confidence: 99%
“…The aggressive enforcement of T21 in Needham, Massachusetts, resulted in a significant reduction in the percentage of youth under age 18 who purchased cigarettes in stores 19. On the other hand, lack of enforcement and monitoring of retailer compliance to T21 in New York City may have resulted in mild or no effect on adolescent smoking 21 29…”
Section: Discussionmentioning
confidence: 99%